2014
DOI: 10.1001/jamapediatrics.2013.4347
|View full text |Cite
|
Sign up to set email alerts
|

A Statewide Medicaid Enhanced Prenatal Care Program

Abstract: Participation in MIHP reduced the risk for adverse birth outcomes in a diverse, disadvantaged population. The study adds to the evidence base for enhanced prenatal care home visiting programs and informs state and federal investments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 52 publications
(47 reference statements)
3
59
0
Order By: Relevance
“…Early enrollment and the dosage of services have been shown to be important components of EPC programs, including MIHP. [15][16][17][18] We previously found that participation in MIHP improved health care utilization for mothers and infants and that early prenatal program enrollment and screening and a dosage of MIHP services reduced the risk of prematurity and low birth weight. 16,18 We tested the hypothesis that participation in MIHP reduced the risk of infant death.…”
Section: What This Study Addsmentioning
confidence: 99%
See 4 more Smart Citations
“…Early enrollment and the dosage of services have been shown to be important components of EPC programs, including MIHP. [15][16][17][18] We previously found that participation in MIHP improved health care utilization for mothers and infants and that early prenatal program enrollment and screening and a dosage of MIHP services reduced the risk of prematurity and low birth weight. 16,18 We tested the hypothesis that participation in MIHP reduced the risk of infant death.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[15][16][17][18] We previously found that participation in MIHP improved health care utilization for mothers and infants and that early prenatal program enrollment and screening and a dosage of MIHP services reduced the risk of prematurity and low birth weight. 16,18 We tested the hypothesis that participation in MIHP reduced the risk of infant death. The large study population allowed for analyses by race, relevant due to the large disparities in birth outcomes and infant mortality (whites 5/1000 versus blacks 12/1000), and separate neonatal and postneonatal analyses, important because causes and potential mechanisms of program effect may be very different in the 2 periods.…”
Section: What This Study Addsmentioning
confidence: 99%
See 3 more Smart Citations